2014
DOI: 10.4314/ijbcs.v8i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of ascorbic acid on azathioprine-induced alteration in the testes of adult Wistar rats

Abstract: The use of azathioprine (AZA) in the prevention of organ rejection during transplantation has been noted in different organs of the body. This study investigates the effect of ascorbic acid on azathioprineinduced alteration in the testes of adult Wistar rats. Thirty male adult Wistar rats were randomly assigned into 5 groups comprising a Control group A and four Treatment groups B to E. Animals in treatment groups B and D received 10 and 20 mg/kg of AZA respectively; while rats in treatment groups C received 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The current study also revealed a marked decrease in the number of sperm in the lumen. Similar results were observed by Onanuga et al (2014). The present light microscopic examination and ultrastructural study of testis treated with GSE plus MTX, and testis treated with GSE plus AZA, showed nearly normal structures in most seminiferous tubules, improvement of spermatogenic cells, Sertoli cell, and primary spermatocytes, except for a few degenerated mitochondria.…”
Section: Discussionsupporting
confidence: 88%
“…The current study also revealed a marked decrease in the number of sperm in the lumen. Similar results were observed by Onanuga et al (2014). The present light microscopic examination and ultrastructural study of testis treated with GSE plus MTX, and testis treated with GSE plus AZA, showed nearly normal structures in most seminiferous tubules, improvement of spermatogenic cells, Sertoli cell, and primary spermatocytes, except for a few degenerated mitochondria.…”
Section: Discussionsupporting
confidence: 88%
“…The current study also revealed a marked decrease in the number of sperms in the lumen. Similar results were observed byOnanuga et al (2014). The present light microscopic examination and ultrastructural study of testis treated with GSE plus MTX and testis treated with GSE plus AZA showed nearly normal structure in most seminiferous tubules, improvement of spermatogenic cells, Sertoli cell, primary spermatocyte except few degenerated mitochondrial.…”
supporting
confidence: 90%
“…This state of oxidative stress is the direct cause of various pathological conditions such as aging and cancer: it is the indirect cause of lipid peroxidation in food. In all cases, the risk is increased with the accumulation of these molecules in the body resulting in a radical chain reaction that degrades vital biological molecules, namely DNA, lipids, proteins and carbohydrates [6][7][8]. Frequent exposure to high concentrations of free radicals can lead to direct damage to biological molecules (protein oxidation and nitration, lipid peroxidation, DNA oxidation), but also secondary lesions due to the cytotoxic and mutagenic nature of the metabolites released during lipid oxidation [9,10].…”
Section: Introductionmentioning
confidence: 99%